Work-related allergies to storage mites in Parma (Italy) ham workers - Federica Tafuro; Erminia Ridolo; Matteo Goldoni; Marcello Montagni; Antonio Mutti; Massimo Corradi (BMJ Open)
Objectives To investigate the role of storage mites in the development of allergic diseases among ham production workers, and to search for early alterations in lung function tests and early inflammation markers in exhaled air. Respiratory allergies due to storage mites have been reported in people with various occupations but, although such mites are unavoidable when curing ham, there are no published data concerning ham production workers.Setting Secondary care.Design Experimental cross-sectional study.Participants 220 participants (110 ham production workers and 110 controls) were recruited.Primary and secondary outcome measures Workers answered a medical questionnaire, and underwent spirometry and fraction of exhaled nitric oxide at 50 mL/s (FeNO50) measurements. Those with allergic symptoms also underwent skin prick tests to determine their sensitisation to airborne allergens. A methacholine test was performed in symptomatic participants when spirometry was normal to assess airways hyper-responsiveness.Results Symptomatic storage mite sensitisation was observed in 16 workers (14.5%) (rhinoconjunctivitis in 15 (63%) and asthma in (4%)) and 2 controls (1.8%; p=0.001). Higher FeNO50 values in exposed symptomatic workers compared with healthy control participants (34.65±7.49 vs 13.29±4.29 ppb; p<0.001) suggested bronchial and nasal involvement, although their lung function parameters were normal. Regardless of exposure, a FeNO50 value of 22.5 ppb seems to be 100% sensitive and 99.4% specific in distinguishing allergic and non-allergic participants. Multivariate analysis of FeNO50 values in the symptomatic participants showed that they were positively influenced by IgE-mediated allergy (p=0.001) and reported symptom severity (p=0.041), and negatively by smoking status (p=0.049).Conclusions Ham processing workers, as well as workers involved in any meat processing work that includes curing, should be informed about the occupational risk of sensitisation to mites.